Peace processes in Northern Ireland and Turkey rethinking conflict resolution - Kadıoğlu, İ. Aytaç ca. 20./21. Jh (Edinburgh studies on modern Turkey, 2020)
This book challenges the notion of 'conflict resolution' in the Northern Irish and Turkish-Kurdish peace processes, both far-reaching ethno-nationalist conflicts in the post-Cold War era. Incorporating fieldwork carried out until 2015, I. Aytaç Kadioglu compares these conflicts during major peace attempts, from early secret talks and semi-official peace initiatives, to multilateral and internationalised conflict-resolution processes through not only main armed protagonists, but also independent third parties. As Brexit re-ignites discussion around the border of Northern Ireland, and as the repercussions of the Syrian civil war on the dynamics of the Kurdish conflict continue to unfold, these two cases are particularly important to the study of conflict resolution. In critically assessing existing literature, this book presents an innovative framework for conflict-resolution processes, suggesting that ethno-nationalist conflicts are too complex to be resolved solely through official negotiations